A New Method to Accelerate PPP Convergence Time by using a Global Zenith Troposphere Delay Estimate Model. (September 2014) - Yao, Yibin; Yu, Chen; Hu, Yufeng
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents a new algorithm to accelerate Precise Point Positioning (PPP) convergence. The main idea is to consider the station tropospheric zenith total delay, which is obtained by a global zenith troposphere delay estimate model, as virtual observation and combine it with phase and pseudo-range observations to formulate observation equations. Without relying on any other external enhancement information, it only requires four satellites to quickly complete the positioning with centimetre-level accuracy. Compared with the conventional method, the new one brings about 15% improvement in convergence time.